2004
DOI: 10.1055/s-2004-822743
|View full text |Cite
|
Sign up to set email alerts
|

Stellenwert von Biofeedback-Training mit kombinierter analer Elektrostimulation bei idiopathischer Stuhlinkontinenz

Abstract: The combination of biofeedback training with anal electrostimulation increases anal squeeze and resting pressures, thus leading to an improvement of clinical incontinence symptoms. Therefore it should be the first choice in the therapy of idiopathic fecal incontinence. A training period of 3 months seems to be sufficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
1
0
2
Order By: Relevance
“…S 1 ), including several systematic reviews (Supplementary Table S 1 ) [ 4 , 17 , 19 , 23 – 36 ]. Twenty-three studies were retrospective chart reviews or prospective case series [ 37 59 ], and four current trials [ 60 – 63 ] were found in trial registries, but not in the literature. Seven RCTs [ 15 , 64 69 ] met at least one exclusion criterion (Supplementary Table S 2 ), and 13 RCTs remained [ 11 , 14 , 16 , 18 , 70 78 ] (Supplementary Tables S 3 to S 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…S 1 ), including several systematic reviews (Supplementary Table S 1 ) [ 4 , 17 , 19 , 23 – 36 ]. Twenty-three studies were retrospective chart reviews or prospective case series [ 37 59 ], and four current trials [ 60 – 63 ] were found in trial registries, but not in the literature. Seven RCTs [ 15 , 64 69 ] met at least one exclusion criterion (Supplementary Table S 2 ), and 13 RCTs remained [ 11 , 14 , 16 , 18 , 70 78 ] (Supplementary Tables S 3 to S 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is a successful key element within our treatment algorithm, even in patients with sphincter damage and neuropathic anal incontinence. [4]. Als weitere Option steht inzwischen die sakrale Nervenstimulation zur Verfügung [5].…”
unclassified
“…B. [1], gesammelt in [2]). Zwar wird in Studien der Druck gemessen, den der Schließmuskel aufbauen kann, es werden Komplikationen von Operationen gezählt und manchmal werden die Patienten gefragt, ob sie kontinent sind [3].…”
unclassified